Low-Level Zoonotic Transmission of Clade C MERS-CoV in Africa: Insights from Scoping Review and Cohort Studies in Hospital and Community Settings - Andrew Karani; Cynthia Ombok; Silvia Situma; Robert Breiman; Marianne Mureithi; Walter Jaoko; M. Kariuki Njenga; Isaac Ngere (Viruses)
Human outbreaks of Middle East respiratory syndrome coronavirus (MERS-CoV) are more common in Middle Eastern and Asian human populations, associated with clades A and B. In Africa, where clade C is dominant in camels, human cases are minimal. We reviewed 16 studies (n = 6198) published across seven African countries between 2012 and 2024 to assess human MERS-CoV cases. We also analyzed data from four cohort studies conducted in camel-keeping communities between 2018 and 2024 involving camel keepers, camel slaughterhouse workers, and hospital patients with acute respiratory illness (ARI). The analysis showed a pooled MERS-CoV prevalence of 2.4% (IQR: 0.6, 11.4) from 16 publications and 1.14% from 4 cohort studies (n = 2353). Symptomatic cases were rarely reported, with most individuals reporting camel contact, and only 12% had travel history to the Middle East. There was one travel-associated reported death, resulting in a mortality rate of 0.013%. The findings suggest a low camel-to-human transmission of clade C MERS-CoV in Africa. Ongoing research focuses on genomic comparisons between clade C and the more virulent clades A and B, alongside the surveillance of viral evolution. This study highlights the need for continuous monitoring but indicates that MERS-CoV clade C currently poses a minimal public health threat in Africa.